Borneol, a novel agent that improves central nervous system drug delivery by enhancing blood–brain barrier permeability. (1st January 2017) - Zhang, Qun-Lin; Fu, Bingmei M.; Zhang, Zhang-Jin
Abstract: The clinical application of central nervous system (CNS) drugs is limited by their poor bioavailability due to the blood–brain barrier (BBB). Borneol is a naturally occurring compound in a class of 'orifice-opening' agents often used for resuscitative purposes in traditional Chinese medicine. A growing body of evidence confirms that the 'orifice-opening' effect of borneol is principally derived from opening the BBB. Borneol is therefore believed to be an effective adjuvant that can improve drug delivery to the brain. The purpose of this paper is to provide a comprehensive review of information accumulated over the past two decades on borneol's chemical features, sources, toxic and kinetic profiles, enhancing effects on BBB permeability and their putative mechanisms, improvements in CNS drug delivery, and pharmaceutical forms. The BBB-opening effect of borneol is a reversible physiological process characterized by rapid and transient penetration of the BBB and highly specific brain regional distribution. Borneol also protects the structural integrity of the BBB against pathological damage. The enhancement of the BBB permeability is associated with the modulation of multiple ATP-binding cassette transporters, including P-glycoprotein; tight junction proteins; and predominant enhancement of vasodilatory neurotransmitters. Systemic co-administration with borneol improves drug delivery to the brain in a region-, dose- and time-dependent manner. Several pharmaceutical forms of borneol have been developed to improve the kinetic and toxic profiles of co-administered drugs and enhance their delivery to the brain. Borneol is a promising novel agent that deserves further development as a BBB permeation enhancer for CNS drug delivery.